Learning with Video in Hypermedia - Chambel, Teresa (2009)
The potential for education of the motion picture was early recognized by many, but technological and use constraints have limited, or perhaps just postponed, the fulfilment of this vision. Significant technological advances and the new tendencies for media convergence and integration are transforming video into a dominant medium, suggesting new ways to support learning activities. The purpose of this paper is to contribute to the understanding of the effective use of video in education, in particular by discussing the role of hypervideo in learning environments. Our approach is based on human cognition concepts, the way media relates to learning, and hypervideo characteristics. These concepts and ideas are being developed and experimented in the context of the Unibase project on interactive and multimedia distance learning